The Primacy of Index in Naming Paradigms. Part I - West, Donna E. E. (Respectus Philologicus, 2015)
This analysis highlights semiotic naming differences between pronouns, nouns, and verbs. It capitalizes on the pivotal role of Peirce's Object in assigning names, and the special character of pronouns to hasten notice of Objects. It showcases Peirce's indexical sign as an individuating instrument, by arguing that nouns do not name the Object uniquely. The indexical sign alone forces attention on unique entities. Their capacity to invoke notice of shifting places via pronouns/verbs is paramount.The findings indicate a particular developmental course: a noticed “something,” classified object, individuated sequence of actions. The naming begins with the most pure Indexes (pronouns), then nouns (which draw upon similar features); afterwards, the verbs emerge to name dynamic event profiles. This illustrates the indispensability of index in the naming process. Advances in deictic individuation establish and reinforce joint attentional ventures: co-signers are compelled not merely to attend to the same Object, but to recognize distinctive participant roles in event structures.